Mekanisme Pelaksanaan Pengurusan Wasiat Tertutup di Balai Harta Peninggalan - Widya Yuniati Siregar; Besty Habeahan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
A will is a legal instrument that enables an individual to determine the distribution of their assets after death. One type recognized in the Indonesian Civil Code (KUHPerdata) is the closed will (testament olograph), written or signed confidentially by the testator and submitted to a notary before four witnesses. This form of will emphasizes secrecy and the protection of the testator’s final intentions, requiring a clear legal framework to ensure its validity and lawful execution. Within this framework, the Balai Harta Peninggalan, or Heritage Hall, functions as a state institution responsible for receiving, safeguarding, unsealing, and executing closed wills after the testator’s death. The institution’s role ensures that the process is orderly, transparent, and legally compliant. This study examines the procedural mechanism for administering closed wills by the Balai Harta Peninggalan, covering the stages from unsealing to execution in accordance with statutory provisions. Using a normative juridical method with statutory and conceptual approaches, the research analyzes the Civil Code, implementing regulations, and legal literature. The findings show that the execution of closed wills under Balai Harta Peeninggalan’s authority is well regulated under Indonesian law and plays a key role in ensuring legal certainty and protecting heirs’ rights. However, administrative obstacles and low public awareness remain significant challenges.